Lactate dehydrogenase activity in Bacteroides fragilis group strains with induced resistance to metronidazole - Presečki Stanko Aleksandra (JOURNAL OF GLOBAL ANTIMICROBIAL RESISTANCE, 2016)
Abstract The aims of this study were to induce in vitro metronidazole resistance in nim-negative Bacteroides fragilis group strains and to determine the lactate dehydrogenase (LDH) activity of the induced strains. A collection of B. fragilis group strains were identified by matrix-assisted laser desorption/ionisation time-of-flight mass spectrometry (MALDI-TOF/MS). Minimum inhibitory concentrations (MICs) for metronidazole were determined by the agar dilution technique. The presence of nim genes was screened by PCR. A sample of 52 nim-negative metronidazole-susceptible strains were selected at random and were exposed to metronidazole in the resistance induction experiment. LDH activity was measured by spectrophotometry. Of the 52 selected strains, 12 (23.1%) acquired resistance to metronidazole. MICs ranged from 8 mg/L to 96 mg/L. Eight of the twelve induced strains displayed decreased LDH activity, whilst only one expressed a significant increase in LDH activity with LDH values of 49.1 U/mg and 222.0 U/mg, respectively. In conclusion, in vitro induction of metronidazole resistance could be selected in nim-negative B. fragilis group strains. A statistically significant decrease in LDH activity was in contrast to previous findings in which, underlying higher metronidazole MICs, an increase in LDH activity compensated for the decreased activity of pyruvate-ferredoxin oxidoreductase (PFOR). These findings could be explained if the induction caused only physiological and not genetic changes. We believe that genetic mutations in the B. fragilis strain that demonstrated an emergent increase in LDH activity were responsible for the increased activity.